Content Analysis of Food Creator @Onebitebigbite Account on Tiktok Social Media - Tegar Syaefur Rohman; Wildan Jidni Abdillah; Nuruzzaman Nuruzzaman (CV. Syntax Corporation Indonesia, 2025)
This study aims to identify how food content creators use communication strategies in TikTok videos to attract attention, engage viewers, and increase interactions. Using content analysis method, this study identifies strategic elements that contribute to effective creator communication. The analysis results reveal that the effectiveness of food content on TikTok depends on various specific communication aspects. Attractive visual support, fast and dynamic narratives, casual and communicative language use, and effective communication strategies to convince audiences are found to be effective in generating video appeal. Furthermore, optimal video shooting techniques, using hooks as attention points at the beginning of videos, and injecting innovative and dynamic editing techniques also play important roles in maintaining audience interest. This research confirms the importance of understanding platform attributes and audience interests when creating content, especially in the food category. These findings can serve as a reference for creators and digital communication practitioners to develop more effective content strategies that align with short video-based social media culture like TikTok.